대퇴 전자하 골절 불유합에 대한 칼날 금속판을 이용한 수술적 치료 - 박윤수(Youn-Soo Park); 김진홍(Jin-Hong Kim); 우경제(Kyung-Jea Woo); 임승재(Seung-Jae Lim) (The journal of the Korean Orthopaedic Association, 2011)
목적: 대퇴 전자하 골절의 치료 시에는 비교적 높은 빈도의 불유합이 발생하는 것으로 보고되고 있으나 불유합의 치료에 대한 연구는 드물다. 이에 저자들은 대퇴 전자하 골절의 불유합에 대하여 칼날 금속판을 이용한 수술적 치료의 임상적 및 방사선학적 결과를 보고하고자 한다. 대상 및 방법: 1997년 4월부터 2008년 10월까지 대퇴 전자하 골절의 불유합에 대하여 칼날 금속판을 이용한 수술적 치료를 시행 받은 환자 중에서 최소 1년 이상 추시가 가능하였던 16예의 환자를 후향적으로 분석하였다. 남자가 8명, 여자가 8명이었으며, 수술 시 평균 연령은 58세(42-77세)였다. 결과의 평가는 골유합 시기, 술 후 합병증, Harris 고관절 점수 및 Sanders 기능적 평가 척도를 이용하여 시행하였으며, 평균 추시 기간은 26개월(12-63개월)이었다. 결과: 최종 추시 시에 16예의 환자 중 15예(94%)에서 골유합을 얻을 수 있었으며, 평균 유합 기간은 7개월(4-11개월)이었다. 골유합을 얻지 못한 1예의 환자는 한차례 더 칼날 금속판을 이용한 내고정술과 골이식술을 시행하였으나 다시 금속판의 파단 및 불유합 소견 발생하여 결국 인공 고관절 전치환술을 시행 받았다. 합병증은 총 2예에서 발생하였는데, 대전자부 점액낭염 1예와 대퇴골 두 무혈성 괴사 1예가 있었다. 이 중 대퇴골 두 무혈성 괴사 환자는 지속적인 동통으로 술 후 2년에 인공 고관절 전치환술을 시행 받았는데, 재수술 시에 대퇴 전자하 불유합 부위의 안정된 골유합 소견을 관찰할 수 있었다. 최종 추시 시에 Harris 고관절 점수는 평균 88점(36-100점)이었으며, Sanders의 기능적 평가 지수에서는 88%에서 양호 이상의 결과를 보였다. 결론: 대퇴 전자하 골절의 불유합에 대하여 칼날 금속판을 이용한 내고정술을 시행하여 매우 높은 비율의 골유합 소견 및 우수한 임상적 평가 결과를 얻을 수 있었다. Purpose: Although nonunion is a relatively common complication in the management of subtrochanteric fractures, there are few studies regarding the treatment of nonunion. The purpose of this study was to evaluate clinical and radiological results for the treatment of subtrochanteric nonunions with a blade plate. Materials and Methods: We retrospectively analyzed 16 cases of subtrochanteric nonunions that were treated with a blade plate between April 1997 and June 2008 and were followed for at least one year after the index operation. There were 8 males and 8 females with an average age of 58 years (range, 42-77 years). Outcome variables included the time to union, postoperative complications, Harris hip score, and the functional rating scale of Sanders. The average follow-up period was 26 months (range, 12-63 months). Results: Union was achieved in 15 (94%) of 16 subtrochanteric nonunions after an average of 7 months (range, 4-11 months). One patient who did not reach union after the index operation underwent repeated surgery with a longer blade plate and bone graft, but this patient was eventually treated with total hip arthroplasty because of persistent nonunion and breakage of the blade plate. Two patients developed complications. One patient had bursitis around the greater trochanter and the other developed avascular necrosis of the femoral head. Of these, the patient with avascular necrosis of the femoral head was treated with total hip arthroplasty because of persistent hip pain 2 years after the index operation. At latest follow-up, the mean Harris hip score was 88 points (range,36-100 points) and the functional rating scale of Sanders was good or excellent in 14 (88%) of 16 patients. Conclusion: The treatment of subtrochanteric nonunions with a blade plate is associated with a very high union rate and good clinical results. KCI Citation Count: 0